AXIAL PISTON MACHINE - CICHON, MARTIN (2009)
An axial piston machine includes a housing and pistons situated in cylinder bores of a rotatable cylinder member, which pistons are supported on a pivoting cradle, the pivoting cradle being supported via at least one pivoting bearing having a bearing gap that has fluid acting on it. The axial piston machine further includes a control and/or regulating device is provided for the control and/or regulation of the fluid pressure in the bearing gap.